2015
DOI: 10.4155/fso.15.62
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular embryo genomic DNA and its potential for genotyping applications

Abstract: Background:Preimplantation genetic diagnosis (PGD) currently relies on biopsy of one or few embryo cells. Our aim was to evaluate the embryo extracellular matrices (spent medium and blastocoele fluid) as source of DNA for embryo genotyping.Results/methodology:We first evaluated the amplifiability and the amount of genomic DNA in spent embryo culture media from day 3 (n = 32) and day 5/6 (n = 54). Secondly, we evaluated the possibility to genotype the MTHFR polymorphism C677T from media at day 5/6 (n = 8) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 19 publications
2
73
1
1
Order By: Relevance
“…Efforts have been made to develop noninvasive approaches for PGS (21,22). Palini et al (23) reported the observation of the existence of DNA in the blastocoele fluid, Gianaroli et al (24) performed a pilot study on chromosome screening using blastocentesis, and Stigliani et al (25,26) observed genomic and mitochondria DNA contents in the culture medium, which were correlated with embryo quality.…”
mentioning
confidence: 99%
“…Efforts have been made to develop noninvasive approaches for PGS (21,22). Palini et al (23) reported the observation of the existence of DNA in the blastocoele fluid, Gianaroli et al (24) performed a pilot study on chromosome screening using blastocentesis, and Stigliani et al (25,26) observed genomic and mitochondria DNA contents in the culture medium, which were correlated with embryo quality.…”
mentioning
confidence: 99%
“…Mitochondrial DNA in particular has been evaluated as marker of blastocyst potential and implantation outcome [59]. More recently, gDNA in Day 5/6 medium has been evaluated for PGD applications, opening the possibility to retrieve genetic information of medical interest from the embryo without invasive procedures [60,61].…”
Section: New Low-invasive Approachesmentioning
confidence: 99%
“…[66][67][68][69] Recently, cell-free DNA has also been detected in blastocyst-spent culture media but no agreement on concordance rate with the genetic status of embryos has been found. [70][71][72][73][74] Although both strategies appear to be attractive methods, they are characterized by some limitations including the incomplete representation of the whole embryonic genome, the potential maternal DNA contamination, the poor nucleic acid integrity and the unknown sampling time points to obtain acceptable amplification rates. 75 Well-designed studies are needed to evaluate the efficacy of cell-free DNA employment on clinical outcomes.…”
Section: Invasive and No Standardized Proceduresmentioning
confidence: 99%